Implementasi Program Kampus Mengajar Angkatan 5 Di SMP Miftahul Ulum Surabaya Dalam Meningkatkan Kompetensi Literasi Dan Numerasi Peserta Didik - Chintya Anggun Lestari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study is to determine the implementation of the 5th generation teaching campus program at SMP Miftahul Ulum Surabaya which refers to the David C. Korten implementation model. This research involved the principal, the 5th generation teaching campus program, and grade 8 students of SMP Miftahul Ulum Surabaya who were selected with snowball sampling techniques. Data collection techniques used in the form of observation, interviews, and documentation. The results of this study showed that the implementation of the 5th generation teaching campus program at SMP Miftahul Ulum Surabaya went well and smoothly and showed an increase in literacy and numeracy in grade VIII students.